Paglambo Gikan sa Yano: Appreciative Inquiry on Strategic Management of a Thriving local Pizza Restaurant - Fabrigar, Christian Noel; Calderon, Luis; Corro, Clint John (12th International Scholars Conference 2025, 2026)
In an increasingly competitive food service industry, local pizza restaurants face mounting challenges in maintaining profitability, customer loyalty, and operational efficiency. With bigger chains expanding rapidly and customer expectations constantly changing, small, independent pizzerias face a tough challenge staying competitive. This research aims to identify best practices and tailored strategies that can enhance the restaurant’s long-term sustainability and competitive edge in a crowded market. This study is grounded in the Resource-Based View and Human Capital Theory. Appreciative Inquiry was used as the primary approach, emphasizing the positive core of the business and its proven practices. Through qualitative research design, specifically employing in-depth interviews, document analysis, and observation, the researchers engaged with key personnel across various organizational levels from first level to top management. The setting of the study is a local thriving pizza restaurant located in the Southern Philippines. Findings revealed several core themes, including the importance of collaborative leadership, standardization of food quality and service, strategic site selection, and menu innovation. The study also highlighted the restaurant's ability to adapt to market trends, maintain internal coherence, and foster a customer-centric culture. These practices were anchored in strong internal resources and a clear vision. For future studies, it is suggested to explore quantitative or mixed-method research on strategic management practices suited for micro and small food service enterprises in local contexts.